THE INOVATIVE DESIGN OF HOMESTAY TO ADDRESS COVID-19 PROTOCOL - I Dewa Gede Agung Diasana Putra; I Made Adhika; Anak Agung Gde Agung Yana (LP2M Universitas Bina Mandiri Gorontalo, 2020)
Homestay in a traditional Balinese house is one crucial accommodation model in Bali that has been an exciting model for travelers. However, since the increase of pavilions in the traditional house for a homestay, the house's traditional component related to the natural air ventilation has already gone from the house. This component related to sustainability in terms of energy is also an excellent component to face the covid-19 pandemic in which the cross circulation of fresh air into the room is an excellent condition to keep the room healthy. This paper explores the cross ventilation of fresh air and the innovation to maintain this cross ventilation in the new pavilions. This paper then field works, interviews, and architectural examinations were carried out in some tourism villages. The settings of homestays and the possibility of design innovations were investigated and analyzed to produce a suitable innovation model to address covid-19 protocol as a prelemary reseach.